2005
DOI: 10.1097/01.ju.0000154351.37249.f0
|View full text |Cite
|
Sign up to set email alerts
|

Using Tumor Markers to Predict the Survival of Patients With Metastatic Renal Cell Carcinoma

Abstract: In patients with clear cell RCC a prognostic model for survival that includes molecular and clinical predictors is significantly more accurate than a standard clinical model using the combination of stage, histological grade and performance status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(132 citation statements)
references
References 17 publications
7
120
1
4
Order By: Relevance
“…However, most of the literature about the utility of CA-IX as a prognostic marker on ccRCC comes from series of patients with metastatic cancer (10)(11)(12), with a lack of series on non-metastatic cancer.…”
Section: Carbonic Anhydrase IX Is Not a Predictor Of Outcomes In Non-mentioning
confidence: 99%
“…However, most of the literature about the utility of CA-IX as a prognostic marker on ccRCC comes from series of patients with metastatic cancer (10)(11)(12), with a lack of series on non-metastatic cancer.…”
Section: Carbonic Anhydrase IX Is Not a Predictor Of Outcomes In Non-mentioning
confidence: 99%
“…In renal cell cancer, PTEN gene expression has been shown to be downregulated in a large percentage of cases, presumably by epigenetic silencing (Brenner et al, 2002;Velickovic et al, 2002). In particular, lack of PTEN expression has been shown to be an independent negative prognostic factor for diseasespecific survival in patients with metastatic renal cell carcinoma (Kim et al, 2005). However, in culture, most of the renal cancer cell lines remain poorly sensitive to rapalogues.…”
Section: Differential Review Of Biological Effects Of Mtor Inhibitionmentioning
confidence: 99%
“…While tumour biology clearly mirrors that of its histopathological features, it is suggested that the molecular profile of the tumour more accurately reflects the biological behaviour of the tumour (Kim et al, 2005). Therefore, individual biomarkers and linked molecular signatures such as those identified in our present study can clearly supplement standard clinical information to provide enhanced prognostication of RCC patients.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, individual biomarkers and linked molecular signatures such as those identified in our present study can clearly supplement standard clinical information to provide enhanced prognostication of RCC patients. To this end, two recent innovative studies have reported the development of a prognostic model that incorporates a panel of malignancy-associated biomarkers (which includes p53, CA9, Ki67, vimentin, CA12, PTEN and gelosin) with standard clinical parameters and where the resultant 'clinical/molecular marker' model, better predicts survival of patients with RCC (Kim et al, , 2005. Specifically, when ranked alongside several conventional RCC staging systems such as Fuhrman grade, TNM and ECOG-Performance Status (PS), the integrated 'clinical/molecular marker' prognostic model demonstrated superior prognostic value than either and/or that afforded by the panel of biomarkers alone.…”
Section: Discussionmentioning
confidence: 99%